2023
DOI: 10.1002/art.42679
|View full text |Cite
|
Sign up to set email alerts
|

Anti–Citrullinated Protein Antibodies With Multiple Specificities Ameliorate Collagen Antibody–Induced Arthritis in a Time‐Dependent Manner

Alejandro M. Gomez,
R. Camille Brewer,
Jae‐Seung Moon
et al.

Abstract: ObjectiveAnti‐citrullinated protein antibodies (ACPAs) are highly specific for rheumatoid arthritis (RA) and have long been regarded as pathogenic. Despite substantial in vitro evidence supporting this claim, reports investigating the pro‐inflammatory effects of ACPAs in animal models of arthritis are rare and include mixed results. Here, we sequenced the plasmablast antibody repertoire of a RA patient and functionally characterized the encoded ACPAs.MethodsWe expressed ACPAs from the antibody repertoire of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Recently, it was reported that ACPA might protect against arthritis progression in mice [43]. These findings were subsequently replicated by three other groups [44 ▪▪ ,45,46], each using other ACPA MoAbs. Likewise, injection of purified ACPA from patients were also reported to have anti-inflammatory effects in the murine arthritis model used.…”
Section: Recent Antimodified Protein Antibody Developmentsmentioning
confidence: 82%
“…Recently, it was reported that ACPA might protect against arthritis progression in mice [43]. These findings were subsequently replicated by three other groups [44 ▪▪ ,45,46], each using other ACPA MoAbs. Likewise, injection of purified ACPA from patients were also reported to have anti-inflammatory effects in the murine arthritis model used.…”
Section: Recent Antimodified Protein Antibody Developmentsmentioning
confidence: 82%
“…It remains to be investigated whether immunisation with acetylated bacterial proteins leads to the onset of symptoms in mice prone to develop arthritis, although it is also conceivable that no arthritis will develop given the recent anti-inflammatory effects of ACPA in murine arthritis models. 17 19 …”
Section: Discussionmentioning
confidence: 99%